ChAdOx1 NiV vaccination protects against lethal Nipah Bangladesh virus infection in African green monkeys - Neeltje van Doremalen; Victoria A. Avanzato; Kerry Goldin; Friederike Feldmann; Jonathan E. Schulz; Elaine Haddock; Atsushi Okumura; Jamie Lovaglio; Patrick W. Hanley; Kathleen Cordova; Greg Saturday; Emmie de Wit; et al. (npj Vaccines, 2022)
Abstract Nipah virus (NiV) is a highly pathogenic and re-emerging virus, which causes sporadic but severe infections in humans. Currently, no vaccines against NiV have been approved. We previously showed that ChAdOx1 NiV provides full protection against a lethal challenge with NiV Bangladesh (NiV-B) in hamsters. Here, we investigated the efficacy of ChAdOx1 NiV in the lethal African green monkey (AGM) NiV challenge model. AGMs were vaccinated either 4 weeks before challenge (prime vaccination), or 8 and 4 weeks before challenge with ChAdOx1 NiV (prime-boost vaccination). A robust humoral and cellular response was detected starting 14 days post-initial vaccination. Upon challenge, control animals displayed a variety of signs and had to be euthanized between 5 and 7 days post inoculation. In contrast, vaccinated animals showed no signs of disease, and we were unable to detect infectious virus in tissues and all but one swab. No to limited antibodies against fusion protein or nucleoprotein antigen could be detected 42 days post challenge, suggesting that vaccination induced a very robust protective immune response preventing extensive virus replication.